ANALYSIS STUDY OF OPEN DATA IMPLEMENTATION TO IMPROVE PUBLIC POLICY MAKING PROCESS IN JAKARTA PROVINCIAL GOVERNMENT BASED ON DYNAMIC GOVERNANCE (Administratio, 2019)
This research explained about open data implementation in Jakarta Provincial Government which is analyzed through a dynamic governance perspective. Open data is a part of government information disclosure to encourage the transparency, accountability, public participation, and also to make a policy right on the target. Jakarta Provincial Government as The Capital City of Indonesia has been implemented of open data through Data Jakarta Portal. The presence of valid and accurate data, it will certainly encourage regional development and produce policies that are right on the target. In practice, government has to be more dynamic and adaptive towards the global changing, so the government can be well prepared. The results of this study indicate that collaboration between Bappeda and Diskominfotik which is reviewed from the perspective of thinking again is not optimal. The conditions of coordination between the two institutions are still weak and the communication that exists between them is less effective. Whereas from the perspective of thinking across, Jakarta Provincial Government runs the process of thinking across by inviting open data experts from partner institutions to add capabilities, both conceptual, managerial, technical, and social capabilities. However, strengthening organizational capacity is not optimal because there is still bureaucratic fragmentation which is an obstacle. Furthermore, in the aspect of thinking ahead, even though Open Data has been included in the RPJMD, it has not specifically explained the direction and future of Open Data in Jakarta Provincial Government. Therefore it is necessary to explain explicitly and imperatively about the development of Data Jakarta Portal for the future.